In vitro studies and preliminary in vivo evaluation of silicified concentrated collagen hydrogels - Desimone, Martín Federico (2011)
Hybrid and nanocomposite silicacollagen materials derived from concentrated collagen hydrogels were evaluated in vitro and in vivo to establish their potentialities for biological dressings. Silicification significantly improved the mechanical and thermal stability of the collagen network within the hybrid systems. Nanocomposites were found to favor the metabolic activity of immobilized human dermal fibroblastswhile decreasing the hydrogel contraction. Cell adhesion experiments suggested that in vitro cell behavior was dictated by mechanical properties and surface structure of the scaffold. First-to-date in vivo implantation of bulk hydrogels in subcutaneous sites of rats was performed over the vascular inflammatory period. These materials were colonized and vascularized without inducing strong inflammatory response. These data raise reasonable hope for the future application of silicacollagen biomaterials as biological dressings.